Profile of an occupation – information technology specialist - Schambeck, Arne [Verfasser] (My University, 2023)
"Information technology specialists work in all areas of computer science and information technology. Their field of deployment is very wide-ranging. In order to take account of the technological shift and of new areas of activity such as big data, robotics, Industry 4.0, cyber physical systems and IT in products, the training occupation was modernised in 2020 and expanded from two to a total of four specialisms. The description covers the tasks of IT specialists and the technological trends characterising the occupation." (author's abstract; BIBB-Doku)
Keywords: S 6.4.9 IT-Berufe; 370; Fachinformatiker; Berufsbeschreibung; Tätigkeitsmerkmal